Non-pharmacological methods in the relief of pain related to the screening and diagnosis of breast cancer: scope review (Research, Society and Development, 2021)
Objective: to map non-pharmacological therapies used in the literature to relieve pain in women undergoing breast cancer screening and diagnosis. Methodology: Scope review study carried out in nine data sources using the descriptors mammography, needle biopsy, complementary therapies and pain. Two independent researchers performed the search for the studies and one researcher applied the inclusion and exclusion criteria and performed the analysis. Studies that answered the research question were included, totaling twelve publications. The extraction of research data was performed using instruments built by the authors that allowed the categorization of the information presented. Results: among the final sample of twelve studies, the non-pharmacological methods used were music therapy, meditation, hypnosis, physical exercise, nursing interventions and therapeutic touch. It was observed that music therapy, physical exercises and nursing interventions were used to reduce pain during mammography, and the other methods found were tested in the biopsy procedure. Conclusion: it was shown that non-pharmacological methods used to relieve pain during screening and diagnosis of breast cancer are effective and can contribute to changes in care protocols as they are an easy-access, low-cost, creative, safe and that provides benefits to women.